Bone formation and growth of climbing perch Anabas testudinieus larvae fed with Zn enriched Artemia nauplii - Ismarica, Ismarica; Setiawati, Mia; Jusadi, Dedi; Suprayudi, Muhammad Agus (Indonesian Society of Scientific Aquaculture (ISSA), 2020)
ABSTRACT The aim of this study was to determine the optimum level of Zinc (Zn) enrichment in Artemia sp. nauplii as a live feed to improve bone formation and growth of climbing perch Anabas testudinieus larvae. The study consisted of four different Zn enrichment levels (0.0, 0.05, 0.1, and 0.15 mg/mL) in Artemia sp.nauplii. The enrichment was performed for 12 hours with the nauplii density of 1 ind/mL. Climbing perch larvae with an average initial length of 1.65 ± 0.15 mm were fed four times daily with the enriched nauplii. For the first 5 days, all larvae were fed with rotifer followed by feeding with enriched Artemia nauplii ad libitum. The results showed that the application of Artemia sp. enrichment at 0.1 mg Zn/mL influenced the bone formation, increased the growth, and improved the fish survival of climbing perch larvae. Feeding with 0.1 mg/mL Zn enriched Artemia nauplii could be recommended as a strategy to improve the bone formation and growth performance of climbing perch larvae. Keywords: Anabas testudineus, Artemia sp., climbing perch, live feed, zinc ABSTRAK Penelitian ini bertujuan menentukan dosis optimum pengayaan seng (Zn) pada naupli Artemia sp. terhadap pembentukan tulang dan peningkatan pertumbuhan larva ikan betok. Penelitian dilakukan selama 18 hari dengan empat dosis pengayaan Zn yang berbeda (0, 0,05, 0,1, dan 0,15 mg/mL) pada naupli Artemia. Pengayaan dilakukan selama 12 jam dengan kepadatan naupli 1 ind/mL. Larva ikan betok dengan ukuran panjang awal rata-rata 1.65 ± 0.15 mm diberi pakan naupli yang diperkaya sebanyak 4 kali sehari. Pada lima hari pertama, semua larva diberi pakan rotifer, diikuti dengan pemberian naupli Artemia yang diperkaya secara ad libitum. Hasil yang diperoleh menunjukkan bahwa pengayaan naupli Artemia sp. dengan Zn 0,1 mg/mL berpengaruh terhadap pembentukan tulang belakang dan dapat meningkatkan pertumbuhan serta meningkatkan kelangsungan hidup larva ikan betok. Pemberian naupli Artemia dengan Zn sebanyak 0.1 mg Zn/mL dapat direkomendasikan untuk perbaikan pembentukan tulang dan pertumbuhan larva ikan betok. Kata kunci: Naupli Artemia sp., ikan betok, pakan alami, seng